THE USE OF PREZI TO IMPROVE THE LEARNING INTEREST OF 10TH GRADE STUDENTS OF SMAN 1 PAREPARE - Kholis, Wahidin Nur; Muhayyang, Maemuna; Munir, Munir (JTechLP: Journal of Technology in Language Pedagogy, 2023)
The purpose of this study was to find out students' interest in using Prezi media in learning English, to find out the increasing interest in learning towards the use of Prezi media in learning English in class X SMAN 1 Parepare. This research is a quantitative study using a pre-experimental design, namely One Group Pre-test Post-test Only design. The population in this study were 324 students with sample of class X.1 totaling 25 students selected using cluster random sampling. Data collection techniques are through the distribution of questionnaires and test. The data were analyzed by descriptive analysis and inferential analysis. The results showed that students' interest in learning English with Prezi media for class X.1 SMAN 1 Parepare was in the very good category. It was proved that the mean score of students’ prequestionnaires was 45.56 and the mean score of students’ postquestionnaires was 56.80. From that data, it could be concluded that the use of Prezi medium could improve students’ learning interest.